Manajemen Bank Sampah: Menjadikan Sampah Bernilai Ekonomi Bagi Masyarakat Pondok Pesantren - Globila Nurika; Dewa Ngakan Gde Wahyu Mahatma Putra; Niajeng Novta Dwi Nafisah; Rifdul Basied (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The Nurul Jadid Islamic Boarding School has a problem with the generation of plastic cup waste from drinks. So far, the waste is only collected and burned. The land/building resources for the waste bank and the existing human resources are sufficient to carry out waste bank activities. However, this condition is not supported by sufficient knowledge and skills in implementing waste management activities through waste banks. Therefore, it is necessary to have community service activities in the form of education, training, and assistance to the managers of Islamic boarding schools and the community in the environment around Islamic boarding schools to carry out waste management activities with a waste bank system. This community service activity is carried out in 3 stages, namely situation analysis partner conditions, implementation of interventions, and evaluation activities. Educational activities showed an increase in participants' knowledge about waste management with the waste bank system by 10,938 points. The training activities showed an increase in the ability of participants to carry out waste bank management activities. Assistance activities for the establishment of a waste bank system which show that the managers of Islamic boarding schools have been able to develop a waste bank organizational system and waste bank management flow. It can be concluded that this community service activity is a very strategic effort in order to prepare participants to carry out activities in waste management starting from the source and making waste have economic value.